Nutritional Properties, Antioxidant and Antihaemolytic Activities of the Dry Fruiting Bodies of Wild Edible Mushrooms Consumed by Ethnic Communities of Northeast India - Merilin Kakoti; Dibya Jyoti Hazarika; Assma Parveen; Samim Dullah; Alokesh Ghosh; Dipankar Saha; Madhumita Barooah; Robin Chandra Boro (Polish Journal of Food and Nutrition Sciences)
A variety of cultivated mushrooms in Northeast India are well known for their taste, nutritional and medicinal benefits. Many wild-growing mushrooms are also consumed due to their exotic flavours and tastes; however, the scientific exploration of their nutritional and bioactive properties is still negligible. In the present study, the 32 wild edible mushroom samples of 11 species collected from different parts of Northeast India were evaluated for their proximate composition, mineral and vitamin (ascorbic acid and riboflavin) contents, antioxidant and antihaemolytic activity, and profiles of organic and phenolic acids. Lentinus sajor-caju and Lentinus squarrosulus had the highest carbohydrate content (49.80 g/100 g dry weight (d.w.) and 46.36 g/100 g d.w., respectively), crude protein content (20.72 g/100 g d.w. and 20.54 g/100 g d.w., respectively) and a considerable content of minerals. The highest fat content was determined in Lentinus velutinus (7.17 g/100 g d.w.). Among the minerals, potassium was found as the most abundant in all the samples. The extracts of L. sajor-caju, L. squarrosulus , and Pleurotus pulmonarius were characterized by the highest antioxidant activity, while these of L. sajor-caju, Pleurotus ostreatus, P. pulmonarius and Agaricus bisporus showed the highest antihaemolytic potential. The HPLC analysis allowed determining the high contents of ascorbic acid and a few organic and phenolic acids such as lactic acid, gallic acid, 3,4-dihydroxybenzoic acid and trans -cinnamic acid in the tested mushrooms. Other compounds viz. citric acid, caffeic acid, riboflavin, vanillic acid, pyruvic acid, and p -coumaric acid were detected with variations. This study established the nutritional and health-promoting benefits of wild edible mushrooms of Northeast India region for consumption as functional foods in the human diet.